Policy-related small-area estimation - Longford, Nicholas T. (South African Statistical Journal, 2015)
A method of small-area estimation with a utility function is developed. The utility characterises a policy planned to be implemented in each area, based on the area’s estimate of a key quantity. It is shown by simulations that the commonly applied composite and empirical Bayes estimators are inefficient for a wide range of asymmetric utility functions. An argument is presented for a closer integration of estimation and (regional) policy making because no single small-area estimator is suitable for a wide range of purposes.